Evaluating captive-release strategies for the Western Burrowing Owl (Athene cunicularia hypugaea) - Breanna E. Pyott; Lauren M. M. Meads; Alexandra L. M. Froese; Stephen D. Petersen; Aimee M. Mitchell; Albrecht I. Schulte-Hostedde (Avian Conservation and Ecology, 2023)
Quantitatively evaluating and monitoring augmentation efforts are critical for conservation success. We formally evaluated the success of two Western Burrowing Owl (Athene cunicularia hypugaea) population augmentation programs in Manitoba and British Columbia by assessing survival of breeding adults, fledging success, and return rates of fledglings. Manitoba’s head-starting program holds hatching year (HY) owls taken from the nests of previous captive-released pairs over winter. After being overwintered in human care, the HY owls are released in pairs as second year (SY) owls. British Columbia has a breeding and release program where owls are bred in facilities; their offspring are then held over winter, paired and soft-released in the spring. Both programs soft-release SY pairs that lay clutches in situ and young are referred to as “wild-hatched owls.” We investigated both individual owl and release site characteristics in relation to our success metrics. In Manitoba, breeding season survival averaged 81%, but no factors investigated had a significant effect on survival. In British Columbia, wild-hatched owls returned more than captive released owls (p < 0.001). Determining the causes behind captive-released owls’ reduced rate of return should be a priority for both recovery programs. Fewer owls returned to release sites with more surrounding cropland. Releases should be prioritized at sites with low percentages of cropland. Interestingly, individuals who returned from migration to form pairs and breed had significantly higher reproductive success than captive-released pairs, suggesting effects of survivor-bias or mate choice. By analyzing post-monitoring data, we have identified opportunities for conservation managers to implement modifications to future release protocols.